Polymorphonuclear leucocyte motility in men with ankylosing spondylitis. - Pease, C T (1989)
The polymorphonuclear leucocyte (PMN) response to a chemotactic or chemokinetic stimulus is enhanced in men with ankylosing spondylitis (AS). This effect does not parallel the severity of disease activity or the size of the acute phase response, and it is independent of non-steroidal anti-inflammatory drug treatment. Polymorph function is normal in HLA-B27 positive brothers of probands with AS and in other HLA-B27 positive individuals in the absence of disease. Polymorph motility is also normal in patients with psoriasis vulgaris or Crohn's disease, indicating that enhanced PMN motility is not a non-specific consequence of all inflammatory disorders.